2010
DOI: 10.3102/0034654310362998
|View full text |Cite
|
Sign up to set email alerts
|

Class Attendance in College

Abstract: A meta-analysis of the relationship between class attendance in college and college grades reveals that attendance has strong relationships with both class grades (k = 69, N = 21,195, r = .44) and GPA (k = 33, N = 9,243, r = .41). These relationships make class attendance a better predictor of college grades than any other known predictor of academic performance, including scores on standardized admissions tests such as the SAT, high school GPA, study habits, and study skills. Results also show that class at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
152
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(212 citation statements)
references
References 77 publications
18
152
4
3
Order By: Relevance
“…Although a positive relationship between attendance and academic performance was identified, motivation cannot be ruled out as a possibility in explaining the results of the current study, as suggested in studies also by Crede et al (2010), Dollinger et al (2008), and Moore et al (2008), though each of these also indicated the general importance of attendance. It is possible that students who attend class are more motivated and hence www.ccsenet.org/ijps International Journal of Psychological Studies Vol.…”
Section: Limitations Summary and Future Researchmentioning
confidence: 50%
See 2 more Smart Citations
“…Although a positive relationship between attendance and academic performance was identified, motivation cannot be ruled out as a possibility in explaining the results of the current study, as suggested in studies also by Crede et al (2010), Dollinger et al (2008), and Moore et al (2008), though each of these also indicated the general importance of attendance. It is possible that students who attend class are more motivated and hence www.ccsenet.org/ijps International Journal of Psychological Studies Vol.…”
Section: Limitations Summary and Future Researchmentioning
confidence: 50%
“…If the results are replicated in further studies, then stronger attendance policies might be considered for university and other courses. Crede, Roch, and Kieszczynka's (2010) meta analysis identified that there was a small but significant increase in grades when attendance was compulsory. This indicates that compulsory attendance could be beneficial in increasing academic performance.…”
Section: Limitations Summary and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature revealed that academic performance is closely related to attendance. These studies were conducted in various settings and, in many instances, in conjunction with other variables (Romer, 1993;Halpern, 2007;Credé, Roch, & Kieszczynka, 2010). This study examines whether students' absenteeism rate influences their academic performance.…”
Section: Attendance and Academic Performancementioning
confidence: 99%
“…6 Crede', Roch and Kieszczynka present various views of the importance of class attendance, but also argue against the importance of attendance in general and mandatory attendance policies in particular. 7 Through quantitative analysis, they demonstrate that class attendance explains large amounts of unique variance in college grades, because of its relative independence from standardized tests and weak relationship with student characteristics such as conscientiousness and motivation. They show that mandatory attendance policies have a small, positive impact on average grades.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%